Cognitive Flexibility as A Moderating Role for Gratitude and Depression in Individuals Who Lost Their Jobs - Temmy Andreas Habibie; Fuad Nashori (Universitas Muhammadiyah Surakarta, 2024)
This study aims to examine the moderating role of cognitive flexibility in the effect of gratitude on depression in individuals who have lost their jobs. A total of 216 respondents (male = 188, female = 28) from various regions in Indonesia participated in this study through purposive sampling technique. In this study, three psychological scales were used including gratitude scale (α = 0.947), depression subtest of the DASS-42 (α = 0.933), and cognitive flexibility inventory (α = 0.794). Moderation analysis revealed that cognitive flexibility played an important role in reducing depression (β = -0.121; p = 0.041), while gratitude did not show a significant role in reducing depression (β = 0.005; p = 0.947). Cognitive flexibility plays a role in reducing depression, regardless of the level of gratitude of individuals who have lost their jobs.